MOBILITY AND CAREER OPPORTUNITIES OF RESEARCHERS ON THE LABOUR MARKET - Natalia A. Shmatko; Galina L. Volkova (Высшее образование в России, 2017)
Abstract. The paper provides an overview of modern concepts of researchers’ mobility and migration, including concepts “brain drain” and “brain circulation”. The mobility is considered as one of the most important drivers of research career on academic and nonacademic labour markets. Using the data from the empirical study of Russian doctorate holders, the paper shows the main trends in international and domestic (intrasectoral and intersectoral) mobility and the impact that mobility has on the career opportunities of young scientists. Mobility rates of Russian doctorate holders are compared with those obtained in the international project “Careers of Doctorate Holders” (OECD, Eurostat, UNESCO Institute for Statistics). The results indicate that the main trends inherent in the Russian academic labour market are similar to those in the European and global labour markets. The findings of study indicates that mobile Russian researchers are more demanded in the national labor market, and are also involved in the “synchronous mobility”, when the scientist can have multiple affiliations and work simultaneously in several countries.